The need for a Canadian database of police use-of-force incidents - Bennell, Craig (Canadian journal of criminology and criminal justice, 2022)
Concerns surrounding the use of force by police officers appear to be growing, fuelled by perceptions that the police use force too frequently, research showing that force is applied disproportionately to members of certain groups, and the view held by some that the mechanisms for holding police responsible for unjustified force are inadequate. In this paper, we advocate for the creation of a national use-of-force database in Canada to gain a better understanding of these issues, adding our voice to those who have already been actively calling for this. We describe some of the potential benefits that would be associated with such a database, including the fact that it would enhance police transparency and accountability, while also increasing our understanding of when and why force is used and what strategies may be useful for reducing inappropriate applications of force. We also highlight some of the challenges we think would be encountered, including mandating nationwide participation, overcoming resistance from the police community, establishing sensible case inclusion criteria, and standardizing data collection. While these are significant challenges, we believe not only that they are possible to overcome but that doing so will provide real value to Canadian society.